THE IMPACT OF SOCIAL ESTRANGEMENT, CONSUMER PERCEPTION, CONSUMER RESONANCE AND PURCHASE INTENTION IN SOCIAL COMMERCE - Yan, Tai-Ge; Lin, Li‑Wei; Guo, Chen-yue (International Journal of Research -GRANTHAALAYAH, 2025)
This paper focuses on the field of social commerce, exploring the internal relationships among social estrangement, consumer perception, consumer resonance, and purchase intention. While the rapid development of social commerce has provided consumers with significant convenience, it has also introduced challenges such as social estrangement, encompassing aspects like information, emotion, and behavior, which hinder consumer interaction and negatively impact purchase intention. Consumer perception, influenced by factors such as product knowledge and brand trust, further affects purchase decisions. Consumer resonance, arising from interactions within the community, is fostered by elements like emotional resonance, information sharing, and group identity, and can significantly enhance purchase intention. Building upon the Theory of Planned Behavior and other frameworks, this study constructs a research model and posits hypotheses regarding the negative impact of social estrangement on purchase intention, and the positive effects of consumer perception and resonance on purchase intention. Through questionnaire surveys conducted on social commerce platforms in Zhejiang and employing data analysis methods including descriptive statistics, correlation analysis, and structural equation modeling, the findings reveal that social estrangement significantly inhibits purchase intention, whereas consumer perception and resonance positively promote it. Additionally, purchase intention enhances the conversion rate in social commerce. This research enriches the theoretical system of social commerce, addresses the research gap concerning social estrangement, and expands the application of consumer behavior theory. Practically, it offers guidance for enterprises to optimize platform functionalities, strengthen brand development, and foster consumer resonance to boost purchase intention and market competitiveness. Future research could delve into aspects such as broadening sample scope, integrating multiple methodologies, refining research models, and examining the impact of emerging technologies.